A video-based system for plantar surface acquisition during gait - Chong, A. K.; Alshadli, D.; AL-Baghdadi, J. A. A.; Milburn, P.; Newsham-West, R. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Video-based systems for digital object surface feature acquisition are commonly used to provide non-contact accurate 3D mapping of objects in motion. A review of the literature shows that these systems are extensively exploited in human movement studies. The shape of the human foot plantar surface during gait can be better studied using 3D surface models and contours. Additionally, surface contact characteristics and peak pressure of the plantar surface can be determined readily using the calculated 3D models. In this article, the processing algorithms, image capture and point cloud creating methods are discussed. Further discussion includes the findings of an investigation into the stance phase of gait and the plantar-substrate contact location. Tests show that the developed video-based 3D surface capture techniques are accurate and reliable.